Effect of BCS and parity on uterine involution, ovarian rebound and various fertility parameters in postpartum dairy cows - SHARMA, AKSHAY; SINGH, MADHUMEET; SHARMA, AMIT; KUMAR, PRAVESH (The Indian Journal of Animal Sciences, 2018)
The objective of present study was to investigate the effect of body condition score and parity on uterine involution, resumption of ovarian cyclicity and subsequent fertility parameters after calving in Jersey crossbred cows. Primiparous (10) and pluriparous cows (13) having normal parturition were examined. Body condition score was recorded at the time of calving and a significant difference was observed between primiparous and pluriparous cows. The monitoring of uterine involution of previous gravid and non-gravid uterine horn and first postpartum ovulatory follicle (OF) and subsequent corpus luteum (CL) was performed by transrectal ultrasound scanning at weekly interval upto 43 days postpartum. Uterine involution was significantly faster in primiparous cows as compared to pluriparous cows. However, ovarian rebound was significantly earlier in pluriparous cows based on the presence of first postpartum OF and subsequent CL. Monitoring of fertility parameters (days to first artificial insemination, number of inseminations per conception and days open) was done until next conception. Days to first artificial insemination and days open were significantly less in pluriparous cows as compared to primiparous cows. Also, the number of inseminations required for conception were less in pluriparous cows. In conclusion, as the parity increases, postpartum fertility parameters improve despite the rapid uterine involution in primiparous cows.